O sistema plasminogênio/plasmina na resolução da inflamação aguda - Ana Luiza de Castro Ribeiro (2015)
Inflammation is a physiological process that leads to changes in the tissue induced by infectious agents or sterile lesions. The recognition of the harmful agent by resident macrophages leads to increased vascular permeability, leukocyte recruitment and release of pro-inflammatory mediators. A persistent inflammatory response can lead to chronic or autoimmune diseases. Thus, the occurrence of an anti-inflammatory process following of resolution to return to tissue homeostasis is essential. The resolution leads to catabolism of proinflammatory mediators, release of proresolving mediators, increased apoptosis of leukocytes and phagocytic capacity of apoptotic bodies by macrophages, a process named efferocytosis. Several studies demonstrate the ability of macrophages to adopt different phenotypes and play important roles in the progression and resolution of the disease. The inflammatory response can be regulated by several factors, such as the components of the plasminogen/plasmin system (Plg/Pla) which, besides acting in fibrinolysis, play an important role in cell migration. While the ability of the plasmin to induce the migration of cells is well known, the cellular profiles are poorly studied. This study investigated the ability of Plg/Pla in inducing leukocyte migration into the pleural cavity of mice and the profile of recruited cells, beyond to evaluated if Plg/Pla increase the efferocytic ability of macrophages and accelerate the resolution of LPSinduced pleurisy. It was also analyzed by Western blot the expression of annexin A1, which acts as a bridge molecule on recognition of phosphatidylserines present in the apoptotic bodies. In addition, we analyzed the expression of plasminogen system proteins during LPS-induced pleurisy. Injection of Plg/Pla induced a time-dependent influx of mononuclear cells, mainly macrophages, in the pleural cavity of mice without a significant increase in the number of neutrophils and lymphocytes. Analysis by flow cytometry showed that these cells are mainly macrophages of anti-inflammatory (M2) and resolving (Mres) profiles without changes in the number of macrophages with pro-inflammatory profile (M1). Furthermore, Plg/Pla increased the efferocytic capacity of both murine peritoneal macrophages and macrophage derived from bone marrow. A possible mechanism was evidenced by the increased expression of annexin A1 after Plg/Pla stimulation in vivo and in vitro. During LPS-induced pleurisy, there was increased expression of á-enolase and Plg in concordance with resolution times. Although the pre or post-treatment with Plg/Pla does not accelerate the resolution of pleurisy, Plg increases the number of mononuclear cells into the pleural cavity, what deserves to be further investigated. The results show that Plg/Pla acts in key points of inflammation resolution (macrophage skew and efferocytosis), which can contribute to the efficient resolution process and consequent return to tissue homeostasis.